Geochronological and structural investigations of the Northern Pelagonian crystalline zone. Constraints from K/Ar and zircon and apatite fission track dating - MOST, T.; FRISCH, W.; DUNKL, I.; KADOSA, B.; BOEV, B.; AVGERINAS, A.; KILIAS, A. (Bulletin of the Geological Society of Greece, 2001)
The northern part of the Pelagonian Zone experienced a polyphase deformation and metamorphism. Four groups of K/Ar biotite and white mica ages document (I) Hercynian emplacement of plutonic rocks, (II) Eohellenic nappe stacking associated with penetrative deformation / recrystallisation, (III) a Paleocene event in the Mesocoic cover rocks in Greece and (IV) a westward movement of West Pelagonian nappes during Eocene to Oligocene time. First zircon/apatite fission track ages clustering around 70 Ma and 45 to 30 Ma.